2018
DOI: 10.1177/000313481808400727
|View full text |Cite
|
Sign up to set email alerts
|

One More Time: Redo Paraesophageal Hernia Repair Results in Safe, Durable Outcomes Compared with Primary Repairs

Abstract: The incidence and causes of failed paraesophageal hernia repairs (PEHR) remain poorly understood. Our study aimed to evaluate long-term clinical outcomes after reoperative fundoplication as compared with initial PEHR. A prospectively maintained institutional hernia-specific database was queried for PEHR between 2008 and 2017. Patients with prior history of PEHR were categorized as “redo” paraesophageal hernia (RPEH). Primary outcomes included postoperative morbidity, mortality, symptom resolution, and hernia r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Approximately 2% (9/536) of the patients underwent surgery for HH recurrence and postoperative dysphagia strictly, excluding EBD for postoperative dysphagia; this number was slightly lower than the 3%–7% reported in Western countries 26‐28 . Kao et al 29 showed that laparoscopic redo surgery can be safely performed, although the operation time is long and the conversion rate is high. In addition, the reoperation was more durable than the first operation and improved the symptoms in most patients.…”
Section: Discussionmentioning
confidence: 91%
“…Approximately 2% (9/536) of the patients underwent surgery for HH recurrence and postoperative dysphagia strictly, excluding EBD for postoperative dysphagia; this number was slightly lower than the 3%–7% reported in Western countries 26‐28 . Kao et al 29 showed that laparoscopic redo surgery can be safely performed, although the operation time is long and the conversion rate is high. In addition, the reoperation was more durable than the first operation and improved the symptoms in most patients.…”
Section: Discussionmentioning
confidence: 91%
“…Recurrence was determined by symptoms, 13,17,21,23,24,28,30 symptoms and use of medical therapy, 14,34,38 symptoms and upper gastrointestinal series, 15,18,27,37 symptoms, upper gastrointestinal series and endoscopy, 32 or symptoms and pH monitoring 19,25,29 . Some studies did not report how recurrence was defined 31,33,36,40,41 …”
Section: Methodsmentioning
confidence: 99%
“…A laparoscopic redo fundoplication (LRF) is a technically demanding operation due to the presence of adhesions and altered anatomy. Although several studies have demonstrated the safety and efficacy of laparoscopic reoperative antireflux surgery, 13–42 large series or randomized trials to support this evidence are still lacking. Therefore, the aim of this systematic review and meta-analysis was to summarize the current available studies and determine the surgical outcomes of LRF.…”
mentioning
confidence: 99%
“…Re-operative intervention for failed fundoplication can be performed through a minimally invasive approach with good results (14,(17)(18)(19)(20). In a recent study performed at the University of Pittsburgh, re-operative results for failed fundoplication were analyzed.…”
Section: Commentsmentioning
confidence: 99%